2018
DOI: 10.1029/2018gl080222
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Electron Precipitation Associated With Pulsating Aurora Observed by VLF Radio Propagation During the Recovery Phase of a Substorm on 27 March 2017

Abstract: Recent studies suggest that electrons with energies up to several hundred keV precipitate into the atmosphere associated with pulsating aurora (PsA). It is debated the highest energy of precipitating electrons associated with PsA. Here we report for the first time that the energy extends to relativistic energies. PsA was observed by THEMIS all‐sky imagers during a substorm that occurred on 27 March 2017. Energetic electron precipitation was detected by very low frequency subionospheric propagation. We found si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Earlier rocket measurements of PsA showed that precipitating electrons have energies between 2 and 140 keV (McEwen et al, 1981; Sandahl, 1984; Whalen et al, 1971). A more recent study by Tsuchiya et al (2018) found that PsA is associated with relativistic electron precipitation with energy range >100 keV using very low frequency (VLF) subionospheric radio wave propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier rocket measurements of PsA showed that precipitating electrons have energies between 2 and 140 keV (McEwen et al, 1981; Sandahl, 1984; Whalen et al, 1971). A more recent study by Tsuchiya et al (2018) found that PsA is associated with relativistic electron precipitation with energy range >100 keV using very low frequency (VLF) subionospheric radio wave propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Miyoshi, Oyama, et al (2015) demonstrated that a few-hundred-keV electrons precipitate into the mesosphere during the pulsating aurora, and the characteristics of chorus waves simultaneously observed by Van Allen Probes well explained such wide-energy electron precipitations. Grandin et al (2017) and Tsuchiya et al (2018) showed that tens-of-keV electrons simultaneously precipitate into the upper atmosphere from ground-based observations. More recently, Miyoshi et al (2021) showed the precipitation of ∼3 MeV electron by LBC associated with pulsating aurora by coordinated observations Arase and the European Incoherent Scatter (EISCAT) radar.…”
mentioning
confidence: 99%
“…The other possible source was the lower-band chorus waves, which could cause pitch-angle scattering of both diff use/pulsating auroral electrons [39][40][41][42][43] and more energetic electrons [44,4]. Energetic electron precipitations due to the chorus wave have been observed by VLF/LF transmitter signals [45] and riometers [46]. Figure 8 shows a dynamic spectrum in the VLF range observed at ATHA at 05:35 UT.…”
Section: Discussionmentioning
confidence: 99%